Peningkatan Hasil Produksi Aspal melalui Optimalisasi Perawatan Mesin AMP Menggunakan Metode Reliability Centered Maintenance - Cut Afrina; Fitriadi Fitriadi (Jurnal Optimalisasi, 2022)
The achievement of the asphalt production target is largely determined by the engine performance. good engine maintenance is one way to improve engine performance. One way to carry out machine maintenance begins with identifying the damage that occurs so that the machine's performance can be predicted to maintain the quality and quantity of good asphalt production. Asphalt production activities are often disrupted due to the low performance of the Asphalt Machinery Plant (AMP) production machine, while the AMP engine is the main engine in production activities. The method used in this research is Reliability Centered Maintenance (RCM). This method is used to determine exactly what actions will be taken for preventive maintenance on each component of the AMP engine. The purpose of this research is to determine the critical components. Provide recommendations for corrective actions using the FMEA method and predict asphalt production results after the application of RCM. The results of this study obtained four critical components that were damaged, namely the RPN value on the Cold Bin 450, Dryer 360, Hot Bin 360 and Genset AMP 350. Recommendations for corrective action given using the FMEA method are checking the load of the material on the conveyor, checking the load, making Operating SOPs and preparing backups by adjusting the crash history. The prediction of the increase in asphalt production obtained after the application of RCM in November was 2689 tons with an increase in production of 46.8%, in December the production results obtained were 4620 tons, an increase of 29.32%, while in January the production results were 4837 tons with an increase in production percentage of 10.26%.